From tin soldiers to Russian dolls : creating added value through services - Vandermerwe, Sandra (Oxford ; Boston : Butterworth-Heinemann, 1993)
From Tin Soldiers to Russian Dolls is based on several years' research into how companies, both in traditional manufacturing and service settings, can gain and maintain customers by adding value to their products through service. The 'tin soldiers' of the title reflects the product-focused attitudes and systems of many companies up until the late 1980s. Immersed in technical innovations and many manufacturing efficiencies they somehow forgot the customer. The 'Russian doll' image reflects the new customer-focused company which sees its people, processes and core markets as a whole, made up of interconnected and interdependent parts. This book will be particularly suitable for senior managers, short courses/executive programmes and MBA courses.
1. Products, tin soldiers and matter -- 2. Customers, Russian dolls and what matters -- 3. The market power is in the services because the value is in the results -- 4. Jumping into the customer's activity cycle -- 5. Building service-intensive networks -- 6. The soft side of know(ing) how -- 7. Managing the stepping-stones to customer satisfaction -- 8. Making services pay their way -- 9. Linking, liaising and leveraging services through technology -- 10. Looking ahead and beyond.
Includes bibliographical references (pages 225-266) and index.
Keywords: Customer services -- Management; Total quality management; Customer services -- Management; Total quality management; Customer services